Hubungan Karakteristik Responden, Daya Beli dan Asal Suku Bangsa dengan Pola Asuh dalam Pemberian Makanan Pendamping Air Susu (MPASI) pada Bayi Usia 0-12 Bulan di Kota Jambi - Reni Mitra Sari; Nur Alam Fajar; Zulkarnai Zulkarnain (Universitas Batanghari Jambi, 2020)
This research aims to analyze the relationship characteristic of respondents, purchasing power and the origin of ethnic groups with the foster pattern in the feeding of milk escort food (MPASI) in infants aged 0-12 months in Jambi city. This research using methods is an observational research with a mixed method research method between qualitative and quantitative research. This research was conducted in several tribes in Jambi city, such as the people of Origin Jambi as the result of the research is characteristic of respondents who have a last education low of 38 people (39.6%), knowledge of MPASI less well as 66 people (68.8%), customs habits (MPASI) less good as many as 45 people (46.9%), not working as much as 77 people ( And the foster pattern of poor MPASI as much as 50 people (52.1%).